Digital Workflow of Computer-Assisted Implant Surgery and Immediate Loading in The Mandibular Anterior Partial Edentulism after Horizontal Bone Augmentation: A Case Report - Meleknaz Arıcı; Figen Öngöz Dede; Doğu Ömür Dede; Mehmet Esad Güven; Varol Çanakçı (Middle Black Sea Journal of Health Science, 2026)
Background: Guided bone regeneration (GBR) improves the feasibility of implant placement, while computer-assisted implant surgery (CAIS) enables optimal 3-D positioning for better esthetic outcomes with implant-supported fixed partial dentures (ISFPD). This case report presents a digital workflow for CAIS and immediate ISFPD loading in a partially edentulous mandibular anterior region following GBR.Case Report: A 20-year-old female patient was referred for rehabilitation of a partially edentulous mandible due to functional, phonetic, and esthetic concerns. The most preventive, durable, and comfortable ISFPD treatment was selected to replace the missing teeth. Insufficient horizontal bone volume was restored using GBR with a block graft from the symphysis region, secured with graft pins, supported by an autogenous and allograft mixture, covered with a collagen membrane, and closed with a repositioned flap. After six months of healing and digital implant planning, two dental implants were placed in the locations of 32 and 42 using a tooth-supported CAIS with a flapless guided surgery protocol and immediately loaded with a screw-retained temporary ISFPD. The temporary ISFPD was modified and replaced with a partially veneered monolithic zirconia definitive ISFPD after a 3-month healing period. The accuracy of implant placement was evaluated using a metrology-grade 3-D analysis software.Conclusion: In cases of insufficient bone thickness, GBR augmentation can effectively increase bone volume, enabling precise implant placement through guided surgery. Lower linear (0.35 - 1.77 mm) and angular (2.19° and 3.18°) deviations suggest that using CAIS can improve the accuracy of implant placement, and it is necessary to achieve predictable implant placement and favorable prosthetic outcomes.